Fructose Intake Related with Serum Uric Acid Level in Young Adults - Desmawati, Desmawati; Fasrini, Ulya Uti; Afriani, Nita; Sulastri, Delmi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
This study aimed to clarify the correlation of fructose intake with uric acid level and blood pressure in young adults. This study used a cross-sectional design, conducted in Padang, West Sumatera province of Indonesia in 2014. The subjects consist of 109 students of Medical Faculty of Andalas University, aged 18–23 years old, were randomly selected to participate. Data on fructose intake were obtained using food frequency questionnaire. Uric acid levels was determined by the enzymatic colorimetric method. Resting blood pressure was measured twice using a sphygmomanometer. Data were analyzed using Rank-Spearman correlation test. The median of fructose intake was 74.3 g (min 23.4–max 160.2). The median of systolic blood pressure was 117 mmHg (min 100–max 145) and median of diastolic blood pressure was 70 mmHg (min 60–max 90). The mean uric acid levels was 5.2±1.56 mg/dl and 25% of the male subject had high uric acid levels. Fructose intake had no significant correlation with SBP (r=0.026; p=0.851) nor with DBP (r=0.051; p=0.712). However, there was a strong correlation between fructose intake with uric acid level (r=0.660; p<0.001). The study found that fructose intake shows a strong correlation with uric acid level but not with blood pressure in young adult.